2015
DOI: 10.1016/j.archoralbio.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ciprofloxacin-containing antimicrobial scaffolds on dental pulp stem cell viability—In vitro studies

Abstract: Objective A combination of antibiotics, including but not limited to metronidazole (MET) and ciprofloxacin (CIP), has been indicated to eradicate bacteria in necrotic immature permanent teeth prior to regenerative procedures. It has been shown clinically that antibiotic pastes may lead to substantial stem cell death. The aim of this study was to synthesize scaffolds containing various concentrations of CIP to enhance cell viability while preserving antimicrobial properties. Design Polydioxanone (PDS)-based e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 28 publications
3
30
0
1
Order By: Relevance
“…Fiber diameter, which is an influential parameter on the analysis of nanofibrous membranes, was obtained using SEM photographs and image analysis program (ImageJ, p1.44). As indicated in the histogram of average diameter (before cross‐linking) in Figure a, although there are no significant changes in the morphology after loading the drug, there was a margin decrease in the mean diameter of fibers from about 236 ± 37 to 221 ± 81 nm in drug‐loaded samples (CIP‐M 7 –M 9 ) due to the decrease in viscosity of the solutions after incorporation of CIP . Moreover, with increasing Seb, a slight drop in the diameter of fibers is observed.…”
Section: Resultsmentioning
confidence: 90%
“…Fiber diameter, which is an influential parameter on the analysis of nanofibrous membranes, was obtained using SEM photographs and image analysis program (ImageJ, p1.44). As indicated in the histogram of average diameter (before cross‐linking) in Figure a, although there are no significant changes in the morphology after loading the drug, there was a margin decrease in the mean diameter of fibers from about 236 ± 37 to 221 ± 81 nm in drug‐loaded samples (CIP‐M 7 –M 9 ) due to the decrease in viscosity of the solutions after incorporation of CIP . Moreover, with increasing Seb, a slight drop in the diameter of fibers is observed.…”
Section: Resultsmentioning
confidence: 90%
“…Kamocki et al . (,b) demonstrated that scaffolds containing reduced concentrations of ciprofloxacin preserve its antimicrobial properties but enhanced the viability and proliferation of human dental pulp stem cells. It has been demonstrated that ciprofloxacin‐containing scaffolds promise as an intracanal medicament to eliminate Enterococcus faecalis biofilms before REPs (Albuquerque et al .…”
Section: Ongoing Research On the Use Of Antibiotics In Repsmentioning
confidence: 99%
“…Electrospinning is known to be a straightforward nanotechnology-based technique capable of fabricating not only tissue scaffolds for regenerative medicine, but also antibiotic-eluting polymer nanofibers for use in drug delivery (10, 2125, 2731). An accumulating body of evidence suggests that antibiotic nanofibers (single, dual, or triple antibiotics) may provide clinical benefit, as substantial antimicrobial properties have been consistently seen when evaluated against dentin biofilm models (2123, 31).…”
mentioning
confidence: 99%